1997
DOI: 10.1002/(sici)1521-186x(1997)18:1<47::aid-bem8>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of children to residential magnetic fields in Norway: Is proximity to power lines an adequate predictor of exposure?

Abstract: The aim of this work was to study the exposure to magnetic fields of children living at different distances from a power line and to evaluate how well theoretical calculations compared with actual exposure. Personal exposure instruments were carried for 24 h by 65 schoolchildren living 28–325 m from a 300 kV transmission line; the current load was 200–700 A. About half of the children attended a school far from the power line, whereas the other half attended a school located about 25 m from the line. Exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 11 publications
2
13
1
Order By: Relevance
“…In the present study, the distance of School B from 500 kV power lines was 94 m. Compared to the reference limit (0.4 µT), the overall intensity of power frequency magnetic fields at the two schools was lower, but the median measurement at School B was 0.2 µT, while the maximum value recorded was close to 0.4 µT. Studies [55], [56] found that children’s exposure to magnetic fields at a school located close to the power lines influenced considerably the time-weighted average exposure to magnetic over 24 h. Furthermore, the power line was the most important source of exposure when the magnetic field was greater than about 0.2 µT [55]. Therefore, we can not afford to ignore the students’ EMF exposure in the School B.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…In the present study, the distance of School B from 500 kV power lines was 94 m. Compared to the reference limit (0.4 µT), the overall intensity of power frequency magnetic fields at the two schools was lower, but the median measurement at School B was 0.2 µT, while the maximum value recorded was close to 0.4 µT. Studies [55], [56] found that children’s exposure to magnetic fields at a school located close to the power lines influenced considerably the time-weighted average exposure to magnetic over 24 h. Furthermore, the power line was the most important source of exposure when the magnetic field was greater than about 0.2 µT [55]. Therefore, we can not afford to ignore the students’ EMF exposure in the School B.…”
Section: Discussioncontrasting
confidence: 48%
“…For a pupil, household appliances, such as computers, TVs, mobile phones and fixed-line telephone are frequent used. Although one child had greater exposure in some specific situations, such as playing computer games, cooking, and, approaching the television to switch the set on or off [55], [66], exposure was rather stable at home and that the children were only seldom exposed to magnetic filed from household appliances due to pattern of use of a child and generated relatively small fields [55], [62].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is important to mention that measuring exposure human to the electromagnetic field using GIS data, is currently considered a valuable method and that the electromagnetic field generated by power lines is a major source of exposure at home. 15,24 Furthermore, the cross-sectional nature of the study design did not permit assessment of the temporal and thus potentially causal relation of the exposure and infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of the study is the use of calculated magnetic fields based on power lines configuration and not on direct measurements of exposure. However, previous studies have shown that, particularly for children, this methodology tends to be substantially adequate in reflecting actual exposure to power lines-induced magnetic fields, and that this source of exposure tends to exceed the contribution of other sources such as home appliances [11], particularly in the case of high voltage transmission lines [12]. Moreover, we collected in the present study the entire residential history of the study subjects, and therefore we were able to estimate their historical exposure status, while assessments based on single measurements (generally for cases of children's residence at diagnosis) might have led to substantial misclassification of exposure [13].…”
Section: Discussionmentioning
confidence: 99%